GenNormas: um processo genérico para a conformidade legal na engenharia de requisitos - Albuquerque, Hidelberg Oliveira (2014)
In software development process, Requirements Engineering is responsible for identifying what are the objectives of the desired product, its features, activities and constraints, based on the understanding of the scenario where this product is used and/or expected behaviors by users. To interact directly or indirectly with the people, the products and the processes impacted by them, are required to comply with the legal regulations related and found in the legal rules or laws. At the organizational level, these regulations determine how business practices should be, which will be reproduced for their products/processes. The Legal Compliance is a requirement imposed on organizations by government departments and their non-compliance may result in legal and financial problems for these organizations. It is the role of Requirements Engineering dealing with legal compliance in these scenarios. In this context, the Nòmos framework extends the i* framework to achieve legal compliance requirements of information systems and business processes. Nòmos proposes a systematic and cohesive method to achieve this goal, from the execution of activities of elicitation, modeling and negotiation of requirements and laws. However, Nòmos was designed to be used in requirements models represented in i*. Since i* is not widely used in industry, dependence on i* can hurt the adoption of Nòmos as a process to achieve legal compliance in Requirements Engineering. In this sense, this work proposes to adapt the process of Nòmos, making it less dependent on i* and more flexible to be used with other modeling languages requirements. So, was created the GenNormas, in order to guide the acquisition of legal compliance of software requirements or business processes specified in other modeling languages, in addition to i *. Finally, to illustrate the use of our approach, it has been applied in the specification of a hypothetical system, connected to the e-commerce domain, applying GenNormas in requirements specification models, such as the Business Process Modeling Notation (BPMN), in Use Case Diagram and the User Stories.